Efficacy of pretilachlor and oxadiazon on weed control and yield performance of transplant Aman rice - Shahabuddin, M; Hossain, MM; Salim, M; Begum, M (Progressive Agriculture, 2016)
Two experimentswere carried out at the Agronomy Field laboratory, Bangladesh Agricultural University, Mymensingh during July to December 2014 to study the effectiveness of pretilachlor and oxadiazon on weed control and yield performance oftransplant aman rice. In experiment I BRRI dhan31and in experiment II BRRI dhan46 was transplanted with eight weeding practices viz., weedy check; one hand weeding; two hand weeding; weed free;Pretilachlor only;Oxadiazon only;Pretilachlor + one hand weeding; and Oxadiazon+ one hand weeding. The design was split-plot with three replications. Eleven weed species were found to be infested in the experimental plots. Although weeds were completely controlled in weed free treatment, it is not practicable.Pretilachlor oroxadiazon with one hand weeding performed the best in terms of weed density and weed biomass over single application of each and even manual weeding. Weeds were completely resistant to weedy check, poorly susceptible to one hand weeding, moderately susceptible to two hand weeding and single application of both herbicide and highly susceptible to both herbicides with one hand weeding while weeds were completely susceptible to weed free treatment. Herbicides produced slight phyto-toxicity which was recovered by two weeks of application. The highest grain yield was recorded from weed free treatment and was statistically identical to pretilachlor oroxadiazon with one hand weeding. Single application of pretilachlor oroxadiazon ranked the third in terms of yield and statistically similar to two hand weeding followed by one hand weeding. Weedy check performed the worst. Progressive Agriculture 27 (2): 119-127, 2016